Multidimensional Analysis of Lung Function Data - Louton, T.; Fischer, J.; Schloms, M. (Methods of Information in Medicine, 1978)
The expiratory lung function, viz PF, FVC, FEV0.5, FEV1 & FEV3, of 627 male and 438 female (aged over 25) visitors at a health fair, was measured with a spirotone. From these measurements, linear regression equations were computed, thus estimating the lung function, given age and height. The adequacy of the estimation as well as the variance structure of the errors was carefully studied. The importance of the independence of the 5-dimensional variance structure from age and height is explained in relation to the proposed use of the model. The regression equations seem to be adequate estimators and the variance structure of the errors is evidently independent of age and height.
Keywords: Expiratory Lung Function; Linear Regression; Spirometrie Standards; Multidimensional Analysis